2002
DOI: 10.2223/jped.825
|View full text |Cite
|
Sign up to set email alerts
|

The influence of poor nutrition on the necessity of mechanical ventilation among children admitted to the Pediatric Intensive Care Unit

Abstract: ResumoObjetivo: determinar a relação entre a influência do estado nutricional de crianças no dia de sua admissão na unidade de terapia intensiva pediátrica (UTIP), com a necessidade, o tempo de ventilação mecânica durante a internação, e a mortalidade em UTIP.Métodos: estudo de coorte, entre 01/07/1995 e 30/06/1999, envolvendo todas as crianças (entre 28 dias e 48 meses de idade), admitidas na UTIP do Hospital São Lucas da PUCRS, e com um tempo de permanência superior a 8 horas. Foram excluídas as crianças com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…16 In malnutrition, muscle function is affected, originating muscle fatigue and a reduction of up to 75% in work intensity and hence resulting in respiratory failure. [17][18] There was no statistically significant difference in mortality among the 3 groups similar to a single center retrospective study conducted by Goh et al on mechanically ventilated children, overweight, obese or severely obese children did not have any significant difference in mortality, length of stay or duration of mechanical ventilation, when compared to patients with normal weight. 19 Present results highlight the prevalence of malnutrition in PICUs and the importance of anthropometry to allow early interventions to be targeted in high-risk critically ill children.…”
Section: Discussionsupporting
confidence: 71%
“…16 In malnutrition, muscle function is affected, originating muscle fatigue and a reduction of up to 75% in work intensity and hence resulting in respiratory failure. [17][18] There was no statistically significant difference in mortality among the 3 groups similar to a single center retrospective study conducted by Goh et al on mechanically ventilated children, overweight, obese or severely obese children did not have any significant difference in mortality, length of stay or duration of mechanical ventilation, when compared to patients with normal weight. 19 Present results highlight the prevalence of malnutrition in PICUs and the importance of anthropometry to allow early interventions to be targeted in high-risk critically ill children.…”
Section: Discussionsupporting
confidence: 71%
“…As is evident from this review of the literature evaluating the impact of nutrition status on outcome, there is a great deal of heterogeneity in how malnutrition and underweight status are defined. While some studies have used weight for age or height for age, the use of weight for length and/or BMI for age, as in the current study, may be a more reliable measure of the nutrition status in children . This heterogeneity in how malnutrition has been defined may account for the differing results among studies.…”
Section: Discussionmentioning
confidence: 92%
“…While the adult literature has shown malnutrition to be associated with increased ICU length of stay and mortality, prior pediatric ICU studies have demonstrated inconsistent relationships between nutrition status and outcome in a variety of populations . In a prospective study from Brazil involving 332 PICU patients <4 years old, malnutrition (defined as height for age <2 SD below the median) was found to be associated with increased need for mechanical ventilation and ICU length of stay, but no difference in mortality was observed . De Souza Menezes et al studied a cohort of 385 PICU patients classified as malnourished if their BMI‐for‐age or weight‐for‐age was 2 z scores below the mean standard value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These and other studies corroborate the ongoing prevalence of malnutrition in the PICU population, which can substantially worsen during hospitalization and has been associated with prolonged mechanical ventilation, increased length of stay, and poor patient outcomes. [6][7][8][9] EN is preferred in those children with a functioning gastrointestinal (GI) tract. 10,11 Demonstrated to be cost-effective, EN is more physiologic and well tolerated by many critically ill children.…”
Section: Clinical Significancementioning
confidence: 99%